1-butanethiol vapor sensing based on gold nanoparticle immobilized on glass slide by digital color analysis. (6th December 2017) - Shokoufi, Nader; Adeleh, Sara
Abstract: We demonstrate that gold nanoparticles (GNPs) immobilized on silanized glass act as an optical sensor that is able to quantify 1-butanethiol vapor. GNPs optical properties in the visible region are dominated by the surface plasmon resonance (SPR). The high affinity between 1-butanethiol and GNPs through Au-s bond leads to change in plasmon feature of GNPs that immobilized on silanized glass and causes absorption decrease at 542 nm in SPR spectrum of GNPs. It can be used as an optical sensor for quantitative detection. In this research, the glass slide surface activated by aminopropyltriethoxysilane (APTES). Spherical GNPs immobilized on silanized glass by silanization agent. The sensor is based on the spectrophotometry and digital color analysis (DCA) through RGB. We monitored R value and linear range 50–700 µ M ( R 2 = 0.97) with 2.05% relative standard deviation and 26.5 µ M value was achieved, for the limit of detection. This method represents advantages of metal gold nanoparticles and solid substrate stability in one package, being inexpensive and low time consuming is another advantage of our method that can be conducted in petrochemical, pharmaceutical industries, and for detection of rotten food in food industries.